EFFICIENCY ANALYSIS OF APPLICATION OF OBJECT BUNDARIS DETECTION METHODS IN MEDICAL IMAGES - KHAVALKO, Viktor; TSAP, Vladyslav; YARCHAK, Andrii (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Very often in everyday life it is necessary to regulate a certain process and maintain a certain state, despite the negative effects on productivity. This is especially true in the medical field, where devices and equipment are increasingly common, on which, after receiving a picture, additional methods of image processing can be applied, before the direct use of boundary detection methods. Most of these devices use simple or complex algorithms to perform tasks.That is why the relevance of studying different aspects of segmentation algorithms, analyzing and comparing different types of medical images, conducting experiments on them, comparing the use of different methods and their settings is unquestionable. In order to conduct experiments and comparative analysis, the article proposes to create a process simulation system that will be regulated by the user. The results made it possible to form recommendations regarding the conditions of specific application of the methods.
Keywords: boundaries detection; medical image; images pre-processing; python